(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
This systematic review compiled the results of experiments that evaluated the training of verbal operants in the acquisition of vocabulary in a second language. The databases Medline Complete, Pubmed, PsycINFO and Web of Science were consulted, on January 7, 2021, without delimiting the year of publication. The keywords used were: “verbal operant*”, “mand”, “tact”, “intraverbal”, “echoic”, “textual behavior”, “taking dictation”, “dictation-taking”, “autoclitic”, “second language", "foreign language", "bilingualism" and "bilingual". Eighteen articles were included, totalizing 21 experiments in the analysis. The results show evidence of the efficacy of tact and intraverbal training, including the emerging responses. The results of listener training are less consistent. There is a lack of studies evaluating echoic, mand and autoclitic training. This review advances by systematizing evidence that points to the efficacy of behavioral techniques for teaching vocabulary in a second language.